Need of Reconsideration of SuPclinical Hypothyroidism and Use of Thyroid Hormones. - Dr. Vikrant patil; Dr. Susma Patil (International Journal of Pharma and Bio Sciences, 2020)
Thyroid disorders being one of the commonest diseases that produce significant burden worldwide, 32% of people suffer from thyroid diseases in India. The American Thyroid Association (ATA) has recommended routine population screening of both sexes at age 35 years and then every five years thereafter for early detection and treatment of Subclinical hypothyroidism (SH). According to the International Classification of Diseases (ICD), SH does not have a separate code, but is typically labelled as “hypothyroidism, unspecified”. As per the data published for a clinical trial, about 90% of the study population with SH have TSH levels between 4 and 10 mIU/L. Around 20-25% of people with normal TSH levels report one or two of these symptoms. The relation between symptoms and biochemical TSH levels remains unclear. Observational data suggest that SH is associated with an increased risk of coronary heart disease, heart failure, and cardiovascular mortality, particularly in those with TSH levels >10 mIU/L. Such associations were not found for most adults with TSH levels of 5-10 mIU/L. So it is very imperative to pass on guidelines over thyroid hormone use in abnormal TSH below 10mIU/L and above 10mIU/L differently. Still abnormality in thyroid gland physiology and biochemical levels of TSH, T3 and T4 are considered as a disorder or disease associated with thyroid. But considering variable presentations of biochemical scenarios in thyroid dysfunctioning with skewed patterns of clinical symptomatology, there is a need to look at this clinical condition in a more rounded way and denote the same as a Thyroid syndrome.